2020
DOI: 10.3390/aerospace7070096
|View full text |Cite
|
Sign up to set email alerts
|

SITAEL HC1 Low-Current Hollow Cathode

Abstract: SITAEL is active in the field of electric propulsion and is involved in the development of different thruster technologies—mainly Hall thrusters (HTs)—of power levels ranging from 100 W up to 20 kW. Low-power HTs are the most effective choice to perform orbit transfer, drag compensation, and de-orbiting maneuvers for small satellites. This paper is dedicated to the activities regarding HC1, the hollow cathode conceived for the 100-W-class Hall thruster under development at SITAEL. Successful test campa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This thermal study uses numerical simulations to describe the thermal behaviour during the cathode ignition phase considering heating via the heater and absence of plasma. Disregarding non-linear effects such as the Schottky effect, the Richardson-Dushman equation states that the temperature of the insert's inner surface would need to be around 1100 • C to achieve an emission current density of approximately 5-6 A cm −2 [1,20,26,27] that is needed for producing an electron current of 2.5 A, that is a benchmark value for the subsequent coupling with the thruster. A trade-off between the manufacturing limitations and structural properties with respect to the geometric features of the modular hollow cathode, such as wall thickness and disk length, results in the use of the selected materials with their respective thermal conductivity.…”
Section: Cathode Thermal Analysis: Modelling and Experimentalmentioning
confidence: 99%
“…This thermal study uses numerical simulations to describe the thermal behaviour during the cathode ignition phase considering heating via the heater and absence of plasma. Disregarding non-linear effects such as the Schottky effect, the Richardson-Dushman equation states that the temperature of the insert's inner surface would need to be around 1100 • C to achieve an emission current density of approximately 5-6 A cm −2 [1,20,26,27] that is needed for producing an electron current of 2.5 A, that is a benchmark value for the subsequent coupling with the thruster. A trade-off between the manufacturing limitations and structural properties with respect to the geometric features of the modular hollow cathode, such as wall thickness and disk length, results in the use of the selected materials with their respective thermal conductivity.…”
Section: Cathode Thermal Analysis: Modelling and Experimentalmentioning
confidence: 99%
“…This parameter can be seen as an indication of how difficult it is for the anode to collect the electrons produced by the cathode [10]. Here, the discharge potential at I a = 0.5 A is larger than in conventional orificed low-current cathodes [26], i.e. typically < 40 V, but unsurprisingly high for an open-end emitter cathode operating at such low mass flow rate [44,45].…”
Section: Variation In Anode Potential and Anode Current Oscillationsmentioning
confidence: 99%
“…Sub-ampere thermionic cathodes operating at emission currents below 1 A are a class of electron emitters [13,26,27] employed with low-power Hall thruster systems, typically operating at < 250 W. Few studies focused on the discharge stability and mode transition in such cathodes [28,29] and the influence of an applied magnetic field on the operation of sub-ampere cathodes in standalone mode was never documented before. Here, an open-end knifeedge LaB 6 emitter cathode is tested in standalone mode with an external disk anode.…”
Section: Introductionmentioning
confidence: 99%
“…As an inert gas, krypton, which has smaller mass, smaller collision cross-sections and higher ionization potential compared to xenon, is much more abundant on Earth than xenon. Therefore, krypton has become one of the ideal alternative propellants to reduce the dependence on the expensive gases and has attracted extensive international attention [3,22,23]. Potrivitu et al systematically tested the low current hollow cathode with krypton and observed the mode transition under several operation conditions [22].…”
Section: Introductionmentioning
confidence: 99%